Flood risk management: Property rights-focussed instruments in Australia. Issue 119 (May 2021) - Sheehan, John; Brown, Jasper
Highlights: Management agreements for private property rights can be effective for using Transferable Development Rights (TDRs) in downstream flood-prone urban areas. Inverse leaseholds are revealed as an innovative instrument for non-urban upstream areas rather than TDRs or compulsory acquisition. TDRs or compulsory acquisition are arguably more suitable for down-stream urban flood-prone areas. Abstract: Flood-prone areas are more often than not held under private property rights. Hence, the purpose of this research is to highlight how crucial private stakeholders are to the effectiveness of any instrument for flood risk and hence directly impact on the effectiveness of flood management and yet, private property rights are rarely highlighted in such schema. Additionally, the location of flood-prone areas upstream or downstream provides an important impulse for the selection of the appropriate instrument to achieve flood risk management. Land in upstream non-urban areas in Australia and in Europe, is on the whole used for purposes such as agriculture or forestry. The value of these upstream non-urban lands is drawn from their economic utility as agricultural or forestry enterprises, and hence capital worth is associated with the actual use of the land holding. This situation is different from downstream urban lands where generally the land value is closely linked to the capital growth potential of the land in situ. For example, land used for commercial or residential purposes in downstream urban locations albeit flood prone invariably has a potential for uplifting value through intensification in some manner or other of the built form. The principal results of Australian field research by the authors (jointly with others) suggests such management instruments for private property rights can be effective using Transferable Development Rights (TDRs) in downstream flood-prone urban areas and inverse leaseholds in upstream non-urban areas. This paper concludes through a focus primarily on the use of inverse leaseholds which are revealed as an innovative instrument for non-urban upstream flood-prone areas, rather than TDRs or compulsory acquisition which are arguably more suitable in down-stream urban flood-prone areas.